1999
DOI: 10.1136/bmj.319.7210.612
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antidepressant drug counselling and information leaflets on adherence to drug treatment in primary care: randomised controlled trial

Abstract: Objectives To evaluate two different methods of improving adherence to antidepressant drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
140
2
7

Year Published

2000
2000
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(154 citation statements)
references
References 17 publications
4
140
2
7
Order By: Relevance
“…10 Two studies have demonstrated that brief medication counseling (albeit provided by nonphysicians) to discuss medication could enhance adherence and improve clinical response. 11,12 Even though forms of collaborative care involving mental health providers within a primary care model have appeared to lead to superior outcomes compared with usual primary care treatment of depression, 13 it is likely that many PCCs will continue to be in a position of providing depression care by themselves and that the financial incentives to do so may play an important role in the time and nature of care they choose to provide. Perception and/ or reality of financial disincentives through lower payment may be a factor contributing to data that indicate a significantly lower percentage of patients treated for depression in the primary care sector receive adequate care than that in the specialty mental health sector.…”
Section: Discussionmentioning
confidence: 99%
“…10 Two studies have demonstrated that brief medication counseling (albeit provided by nonphysicians) to discuss medication could enhance adherence and improve clinical response. 11,12 Even though forms of collaborative care involving mental health providers within a primary care model have appeared to lead to superior outcomes compared with usual primary care treatment of depression, 13 it is likely that many PCCs will continue to be in a position of providing depression care by themselves and that the financial incentives to do so may play an important role in the time and nature of care they choose to provide. Perception and/ or reality of financial disincentives through lower payment may be a factor contributing to data that indicate a significantly lower percentage of patients treated for depression in the primary care sector receive adequate care than that in the specialty mental health sector.…”
Section: Discussionmentioning
confidence: 99%
“…Elles confirment qu'un partage des soins apporte des bénéfices supérieurs à une intervention d'un seul professionnel (Katon et al, 1999 ;Hunkeler et al, 2000 ;Katzelnick et al, 2000 ;Walker et al, 2000 ;Hedrick et al, 2003). Les patients avec une dépression majeure répondraient le mieux aux interventions axées sur la collaboration (Katon et al, 1995 ;1996 ;Peveler et al, 1999 ;Swindle et al, 2003). Bien que les études soient encore peu nombreuses (Craven et Bland, 2006), des résultats probants ont aussi été signalés pour les troubles graves de santé mentale.…”
Section: Modèles D'organisation Et Effets Associésunclassified
“…Both programs led to modest, but significant, improvements in clinical outcomes compared to usual primary care. Peveler et al (1999) have recently reported that brief medication counselling provided by a nurse resulted in significantly greater adherence to antidepressant treatment. For patients with more severe depression who were also prescribed adequate doses of medication, this greater adherence was associated with improved clinical outcomes.…”
Section: The Challenges Of Implementationmentioning
confidence: 99%